2006
DOI: 10.1111/j.1445-2197.2006.03757.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Prosthetic Complications After Unipolar Hemiarthroplasty

Abstract: The results of this study support the use of the CT prosthesis for the management of femoral neck fractures to reduce the high incidence of intraoperative periprosthetic fractures and associated requirements for early reoperation experienced with the UAM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 12 publications
4
22
0
2
Order By: Relevance
“…The development of thigh and groin pain is a reliable marker of prosthesis failure [2] often occurring secondary to prosthetic stem loosening [4,7,9,10]. This complication is avoided by using a cemented hemiarthroplasty [3][4][5].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The development of thigh and groin pain is a reliable marker of prosthesis failure [2] often occurring secondary to prosthetic stem loosening [4,7,9,10]. This complication is avoided by using a cemented hemiarthroplasty [3][4][5].…”
Section: Discussionmentioning
confidence: 98%
“…Divide the width of the stem by the width of the canal. have shown that careful monitoring and aggressive fluid resuscitation significantly reduce the negative effects of cement-associated complications [3,4,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in use of cementless monoblock implants was ascribed to poorer outcomes (in terms of loosening, pain, periprosthetic fractures) and higher revision rates. 5,[7][8][9][10] The more expensive bipolar implants have little benefit over unipolar implants. 6,[11][12][13] Usage of the Thompson prosthesis is also in decline, as conversion and revision of the Thompson prosthesis for dislocation, infection, acetabular erosion, and periprosthetic fracture is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 For the Thompson hemiarthroplasty, dislocation rates range from 0 to 7%. 10,[21][22][23] Early dislocation is associated with high mortality (30-75%). 17,21 Regarding limitations, this study was observational and hence prone to selection bias and confounding by indication.…”
Section: Discussionmentioning
confidence: 99%